Proceedings of 2010 IEEE International Symposium on Circuits and Systems 2010
DOI: 10.1109/iscas.2010.5537144
|View full text |Cite
|
Sign up to set email alerts
|

Adiabatic SRAM with a shared access port using a controlled ground line and step-voltage circuit

Abstract: An adiabatic 64-kb SRAM circuit with shared reading and writing ports was designed, which enables gradual charging and discharging while maintaining a large VDD so that the problems of V T variation and electromigration in the nanocircuit can be solved. In the writing mode, the voltage of the memory cell ground line is increased to VDD/2 gradually, and the nMOSFET is turned off so that the memory cell ground line is set in a high-impedance state. Data can then be written easily by decreasing the voltage of one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 6 publications
0
21
0
Order By: Relevance
“…One is for designing the memory cell ground line voltage and therefore the remaining for charging the word line voltage adiabatically. Spontaneous step voltage formation is confirmed experimentally [3]. Hong Li, Linfeng Li, and Jianping Hu in 2010 showed that with rapid technology scaling, the proportion of the static power consumption catches up with dynamic power consumption bit by bit.…”
Section: Literature Reviewmentioning
confidence: 84%
“…One is for designing the memory cell ground line voltage and therefore the remaining for charging the word line voltage adiabatically. Spontaneous step voltage formation is confirmed experimentally [3]. Hong Li, Linfeng Li, and Jianping Hu in 2010 showed that with rapid technology scaling, the proportion of the static power consumption catches up with dynamic power consumption bit by bit.…”
Section: Literature Reviewmentioning
confidence: 84%
“…This is because 3VDD/4 can be comparatively easily generated using a tank capacitor circuit without energy dissipation [5]. In this case, VRP in Fig.…”
Section: Snm Simulation Resultsmentioning
confidence: 99%
“…The cell size is 1.72 µm × 4.62 µm. There is no area penalty compared with the previous circuit [5].…”
Section: Sram Circuit Structurementioning
confidence: 96%
See 2 more Smart Citations